The Covid-19 Pandemic and Developing the Legal Certainty on Bankrupcy for Health Institution in Indonesia - Krista Yitawati; Adi Sulistiyono; Pujiono (Indian Journal of Forensic Medicine & Toxicology, 2021)
This research aims to analyze how to develop the legal certainty for health institution during the Covid-19pandemic period. The method used in this research is the normative research method, which analyzes therelated constitutional regulations and legal materials. In handling the impacts of the Covid-19 pandemicwhich leads to the weakening of the economy, the government has issued some economic stimuli whichare not limited to direct cash aid to the impacted people, but also relaxation and restructurization programsfor health institution and their business organs. The writer concludes that those things are not enough tocope with the bankruptcy which threatens the nation. Because of that, there needs to be restructurizationagreements between the health institution. This is because until now, the Constitution on Bankruptcy andthe Postponement of Debt Payment Obligations are the latest legislations which regulate the debtors andcreditors’ relation regarding their financial obligations during a financial crisis during the period of theCovid-19 pandemic to protect the health institution.